Peramalan Permintaan dengan Metode Time Series di PT. Margo Mitro Joyo - Muhammad Iqbal; Indah Wahyu Utami; Ringgo Ismoyo Buwono (Jurnal Rekayasa Proses dan Industri Terapan, 2024)
Demand forecasting is one of the company's efforts as a basis for making strategic business continuity decisions. The condition of fluctuating demand makes the stock in PT. Margo Mitro Joyo becomes excess or runs out. Based on conditions it is necessary to forecast the demand for LKS. So that stock buildup that occurs at PT.Margo Mitro Joyo can be overcome. From the problems above, the purpose of this research is to find out the number of forecasting requests for Student Worksheets (LKS) in the next period. The analysis was carried out using 2 time series methods , namely weight moving average and single exponential smoothing. So obtained for demand forecasting respectively 971,025.62 and 994,421.12. and then determined by taking into account the smallest error value.